Successfully Integrating Climate Change Education into School System Curriculum - Scallion, M. (AGU Fall Meeting Abstracts, 2017)
Maryland's Eastern Shore is threatened by climate change driven sea level rise. By working with school systems, rather than just with individual teachers, educators can gain access to an entire grade level of students, assuring that all students, regardless of socioeconomic background or prior coursework have an opportunity to explore the climate issue and be part of crafting community level solutions for their communities. We will address the benefits of working with school system partners to achieve a successful integration of in-school and outdoor learning by making teachers and administrators part of the process. We will explore how, through the Maryland and Delaware Climate Change Education, Assessment, and Research Project, teachers, content supervisors and informal educators worked together to create a climate curriculum with local context that effectively meets Common Core and Next Generation Science Standards. Over the course of several weeks during the year, students engage in a series of in-class and field activities directly correlated with their science curriculum. Wetlands and birds are used as examples of the local wildlife and habitat being impacted by climate change. Through these lessons led by Pickering Creek Audubon Center educators and strengthened by material covered by classroom teachers, students get a thorough introduction to the mechanism of climate change, local impacts of climate change on habitats and wildlife, and actions they can take as a community to mitigate the effects of climate change. The project concludes with a habitat and carbon stewardship project that gives students and teachers a sense of hope as they tackle this big issue on a local scale. We'll explore how the MADE-CLEAR Informal Climate Change Education (ICCE) Community of Practice supports Delaware and Maryland environmental educators in collaboratively learning and expanding their programming on the complex issue of climate change. Participants will learn how to include climate change education as part of a larger ecological exploration, giving students and teachers local context to this global issue and memorable outdoor hands-on experiences and student driven adaptation projects.
Keywords: 0805 Elementary and secondary education; 0815 Informal education; 4327 Resilience; 6334 Regional planning; EDUCATION; NATURAL HAZARDS; POLICY SCIENCES